Adopting law school pedagogy into teaching and learning of dentistry- my Melbourne experience / Mas Suryalis Ahmad - Ahmad, Mas Suryalis (Faculty of Dentistry, 2015)
In 2014, I was fortunate to be accepted into the fully-funded Specialist Certificate in Teaching and Melbourne Teaching Certificate programs at Melbourne Graduate School of Education, ranked world's second-best institution in the field of educational study (QS Top Universities, 2014). In the midst of completing my PhD study at the University of Melbourne, I was determined at taking advantage of the opportunities and gaining as much experience as possible that the University could offer in an endeavor to improve the quality of dental education and practice back home. Meeting other current and future leaders in education, I was overwhelmed by the unique differences portrayed in relation to our academic, career and cultural backgrounds, as well as the enthusiasm expressed by each of the participants. This further inspired me to be adamant in adopting such diversity into establishing a symbiotic relationship that would lead to the advancement of higher education…